Mode of Actions of Bisphosphonates in Dental Implant Procedure: An Overview - Krishna Nanda1 , Gopal Krishna Choudhury2 , Rasmita Kumari Samantaray1 , M. Krishna1 , Sneha Bharadw (Institute of Medico-legal Publications Pvt Ltd, 2020)
Bisphosphonates (BP) are the most commonly used drug forthe past few years for the treatment of varioustypes of bone disorders and malignancies. Osteonecrosis of the jaw (ONJ) is most devitalizing but still nothas been properly acknowledged as of now. These drugs suppress bone turnover by decreasing osteoclasticactivity. This article points in featuring the key and pharmaco-physiological system of activity of bothN2 and non N2 bisphosphonates on bone and activity of bisphosphonates on dental implants, particularlytheir commitment in success of the implant and the present suggestions and rules for implant treatment inpatients who are on bisphosphonate therapy. This article also includes the prevention and management fordecreasing the cumulative IV bisphosphonate dose, stoppage of bisphosphonates before any invasive dentaltreatment, and in ONJ using serum beta-CTX-1 in assessment of risk. “Drug Holiday” for the invasive dentalprocedure is incorporated as well.